Aktivitas Digital Public Relations PTPN I Regional II melalui Instagram - Adawiyah, Latifa Wahyuniawati; Fakhruroji, Moch; Risdayah, Enok (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This research aims to determine the digital public relations activities of PTPN I Regional II in disseminating corporate action information via Instagram @ptpnviiiofficial. Researchers describe how corporate action information is disseminated in the context aspect, how corporate action information is disseminated in the communication aspect, how corporate action information is disseminated in the collaboration aspect, and how corporate action information is disseminated in the connection aspect via Instagram @ptpnviiiofficial. This research uses descriptive methods, a qualitative approach, and a constructivism paradigm. Data collection through in-depth interviews and observations. The results of this research show that digital public relations activities carried out via Instagram @ptpnvviiioffcial are in accordance with the 4C concept initiated by Chris Heuer. Keywords : Digital Public Relations; Information Dissemination; Instagram.